Legal Study of Energy Management and Environmental Conservation in the Islands Region Based on Human Rights - Tianotak, Nasarudin; Tjoanda, Merry; Laturette, Adonia Ivonne; Latupono, Barzah; Ariani, Nevey Varida (Jambe Law Journal, 2025)
Equal distribution of energy is still not truly realized for communities in remote areas in island provinces, especially Maluku. The reality shows that recht idee is still part of the long struggle of Indonesian society, especially in eastern Indonesia. Scientific studies regarding energy justice are a relatively new object of study. In fact, legal research regarding the influence of island cluster development on energy distribution in archipelagic provinces has never been carried out before. For this reason, this research was carried out to answer legal problems related to the design of equitable energy fulfillment based on human rights. The research method used is normative juridical research. Based on the research, it was found that fair energy management in fulfilling human rights in archipelagic provinces should be based on the application of norms and the aim of establishing norms in the context of protecting human rights and humanitarian aspects based on the principles of: (1) The principle of equality; (2) Community participatory principles; (3) transparent principle; (4) principles for implementing the protection of Human Rights; (5) the principle of justice in regulations for island provinces; (6) Principles of utilizing renewable technology and resources.